Humans and Nile crocodiles along the Kunene River, Namibia: population dynamics and socio-ecological interactions - Le Roux, Johannes Lucas (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScConEcol)--Stellenbosch University, 2023.